teacher as a guide of children's competence with peers - File, N (Child & youth care forum)
A comparison is made of recommendations found in the literature for the role teachers can adopt to promote children's competence with peers and observational evidence of how teachers mediate peer interactions in the classroom. While the teacher's role as a mediator is recommended, limited empirical evidence suggests that teachers rarely intervene in children's peer play. (Original abstract-amended)